Flavonoids, anthocyanins, phenolamides, benzoxazinoids, lignans and alkylresorcinols in rye (Secale cereale) and some rye products. (January 2018) - Pihlava, Juha-Matti; Hellström, Jarkko; Kurtelius, Tuula; Mattila, Pirjo
Abstract: Besides dietary fibre, rye ( Secale cereale ) grains are rich source of various phytochemicals such as phenolic acids, lignans and alkylresorcinols. The major aim of this study was to gain new insight into certain less studied phytochemicals e.g. flavonoids, anthocyanins, phenolamides and benzoxazinoids in wholegrain rye and its milling fractions as well as in selected rye products by ultra performance liquid chromatography combined with quadrupole time-of-flight mass spectrometery (UPLC-QTOF). In addition, quantitation of total flavonoid content, anthocyanins, major benzoxazinoids and alkylresorcinols in the rye samples was accomplished by high performance liquid chromatography with a diode array detector (HPLC-DAD). Although the concentration of flavonoids in rye was low compared to, e.g. berries and vegetables, the chemical diversity of flavonoids was high. Various phenolamides were also tentatively identified from rye and rye samples. High concentrations of benzoxazinoids were found in rye malt flour, coarsely ground rye malts and the traditional Finnish dish, mämmi . Highlights: Rye and rye products were analyzed for selected phytochemicals. A number of flavonoids were tentatively identified in rye and rye products. Rye contains also a wide variety of phenolamides, benzoxazinoids and lignans. Alkylresorcinols were found in all rye products and they appear to withstand food processing well.